2018
DOI: 10.1155/2018/5735632
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Neurodevelopmental Outcome in Preterm LBW Infants with Sepsis in India: A Prospective Cohort

Abstract: Objective Neonatal sepsis is associated with abnormal neurodevelopmental outcomes but not with poor growth at 9 to 15 months of corrected age in LBW infants. Design, Setting, and Participants This is a prospective cohort study involving 128 eligible preterm low-birth-weight (LBW) infants admitted during the period of 2013-2014 to the Durgabai Deshmukh Hospital and Research Center. All patients were followed up in the outpatient Department of Pediatrics. They were divided into the sepsis and nonsepsis group. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“… 11 , 13 , 14 Likewise, another study described neonatal sepsis with NEC to be associated with increased neurodevelopmental impairment in low birth-weight survivors manifesting as CP. 16 Several human and animal studies have verified the presence of bacterial exotoxins-induced cytokine-release from microglia and astrocytes, resulting in a systemic inflammatory response syndrome, which further increases the blood-brain barrier permeability causing neuronal damage and apoptosis. 34 - 37 The consequent arterial hypotension and the lability of blood pressure during sepsis, coupled with coagulopathy, lead to cerebral ischemia-reperfusion injury impairing neuronal oxygenation and cerebral autoregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 13 , 14 Likewise, another study described neonatal sepsis with NEC to be associated with increased neurodevelopmental impairment in low birth-weight survivors manifesting as CP. 16 Several human and animal studies have verified the presence of bacterial exotoxins-induced cytokine-release from microglia and astrocytes, resulting in a systemic inflammatory response syndrome, which further increases the blood-brain barrier permeability causing neuronal damage and apoptosis. 34 - 37 The consequent arterial hypotension and the lability of blood pressure during sepsis, coupled with coagulopathy, lead to cerebral ischemia-reperfusion injury impairing neuronal oxygenation and cerebral autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Similarly, gastrointestinal infections like necrotizing enterocolitis (NEC) may trigger systemic inflammatory response resulting in significant neuronal injury with neurodevelopmental implications visible at 18–22 months follow-up. 7 , 13 - 16 …”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that LBW was a predictor of stunting in children aged 0-11 months (Sartika et al, 2021). Babies born with low birth weight have a very high risk of growth deficiency (Pawar et al, 2018). Low birth weight is an indication of nutritional deficiency in the baby while in the womb (Zhao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant association between neonatal sepsis, birth asphyxia, convulsions andNDD. [9][10][11] Studies also reported that the children with severe acute malnutrition, and lower head circumference were significantly associated with developmental delays. 12,13…”
Section: Multiple Nddsmentioning
confidence: 99%